Global action, but national results: strengthening pathways towards better health outcomes for non-communicable diseases. Issue 4 (8th August 2021) - Magnusson, Roger; Patterson, David
ABSTRACT: Global governance of non-communicable diseases (NCDs) has moved beyond the World Health Organization (WHO) to become a shared responsibility of WHO, the United Nations General Assembly, and other willing stakeholders. Despite the significant attention NCDs have received, progress towards global goals and political commitments remains disappointing. This lack of progress calls for greater attention to be given to how actions taken at the international level can lead to improvements in health at the country level. This paper reviews progress in the global response to NCDs by highlighting the role of pathways – both current and potential – for translating global aspirations into national actions that improve health outcomes. Important pathways to national action include the development of normative instruments, political accountability mechanisms, provision of economic support and technical assistance, and other forms of engagement we refer to as 'institutional pathways'. We find that global leadership on NCDs has focused predominantly on generating a suite of normative instruments for influencing national policy, together with global targets and reporting processes but with inadequate development assistance for NCDs, or investment in capacity building. We point to the distinctively legal and regulatory nature of many priority interventions identified by WHO for NCD prevention and control, arguing that legal capacity building of both government and civil society stakeholders is a vital, cost-effective yet neglected pathway for strengthening national responses. We outline a modest vision for global, regional and national leadership in capacity-building and in promoting the role for law in NCD prevention and control.